Facial feminisation surgery in NHS Scotland. Issue 10 (December 2021) - Regan, A.; Kent, S.; Morrison, R.
Abstract: Facial feminisation surgery (FFS) is integral to the management of transgender adult females. Literature detailing the conduct and outcomes of FFS is lacking. The aim of this project was to review surgical practices in NHS Scotland. We identified Gender Identity Clinics throughout Scotland. These clinics were then contacted to discuss which services were available regarding FFS and to whom they refer patients. Retrospective review of electronic case notes between June 2014 and June 2019 was carried out and data was recorded on patient demographics, procedures employed, surgical complications, and postoperative outcome. FFS was carried out in two centres. Sixty patients received FFS during the study period, in 160 separate surgical procedures. Patients were all transitioning from natal biological male to female gender, with an average age of 36 years. The most common procedure was rhinoplasty (n = 36). Surgical complications occurred in eight procedures, and negative outcomes were recorded in 12/88 operating sessions. Increasing demand for surgery was noted throughout the study period. These results suggest that a wide variety of procedures are used, and that FFS is well accepted with relatively few surgical complications and negative outcomes. In depth understanding of patient's perceptions and views of their experiences, alongside objective measures, are essential to determine the impacts of FFS.